Psychological Well-being and Islamic Philanthropy: Reciprocal Effects on Individual and Community Welfare in Muslim Societies - Mutia Aini Ahmad; Masyhuri Masyhuri (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2025)
This study aims to analyze the influence of psychological well-being on philanthropic behavior within the context of Islamic philanthropy. Psychological well-being, encompassing emotional, cognitive, and social aspects, has been demonstrated to play a significant role in motivating individuals to engage in social and philanthropic activities. Utilizing a qualitative approach through literature review, this research explores the relationship between psychological well-being and philanthropy, with a focus on Islamic religious values such as altruism, social connectedness, and a culture of sharing. Data was collected from various academic sources including articles, books, and scientific publications. The study identifies major patterns indicating that individuals with positive psychological well-being tend to be more involved in philanthropy, particularly through acts such as zakat, sadaqah, and waqf. Thematic analysis reveals that Islamic religious values and social connectivity strongly reinforce individual motivation to participate in philanthropy, which in turn contributes positively to community well-being. This research offers new insights into how psychological and Islamic cultural factors mutually support the strengthening of a sharing culture within Muslim societies and provides important theoretical contributions to the study of Islamic philanthropy and social welfare